(untitled) (Bangladesh Journal of Medical Science, 2023)
Objectives: The objective of this work is to assess the psychological impact of Covid-19 through the study of all variables likely to influence the mental health of patients declared positive for Covid-19. This investigation aims to integrate a protocol of psychological therapeutic followup of patients, which is as essential as medical follow-up. Methods: Analytical study of the psychological impact of Covid-19 on patients treated in a health center in the province of Kenitra of Morocco over a period of 6 months. Results: The follow-up of patients declared positive for Covid-19, reveals that, although the majority have never had a psychological or psychiatric history, 38% have stress, 49% anxiety and 51% sleep disorders. Conclusion: The study shows that the Covid-19 pandemic generates alongside the physical symptoms, a significant psychological impact on patients Characterized by anxiety, insomnia and post-traumatic stress. Therefore, care integrating the psychological follow-up of patients is necessary. Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 895-901